Soil nutrient concentrations influence micronutrient concentrations in Eragrostis curvula seeds. - Nqobile Motsomane; Rob Slotow; Anathi Magadlela (PLoS ONE)
Food insecurity often results in malnutrition, manifesting as micronutrient deficiencies that disproportionately affect children under five, impairing their cognitive and physical development. While staple crops supply necessary calories and basic nutrients required for life sustenance, they frequently lack essential micronutrients needed for overall health, necessitating alternative food sources to address food insecurity and malnutrition. This study investigated the potential of Eragrostis curvula seeds as a micronutrient-rich addition to existing food systems and used analyses of covariance to evaluate the influence of soil characteristics on seed nutrient concentrations between two grassland sites in South Africa's Gauteng province: Jameson Park and Kaydale. Populations of E. curvula were identified in Jameson Park and Kaydale, Heidelberg, where rhizosphere soils from selected plants and seeds were harvested for nutrient concentration and soil characteristics analysis. Eragrostis curvula seeds were rich in essential micronutrients, including phosphorus (5041.5-5921.7 mg/kg), iron (72.2-145.4 mg/kg), potassium (4490.5-5531.2 mg/kg), zinc (44.9-65.4 mg/kg), copper (8.6-10.2 mg/kg), calcium (2978.4-16339.1 mg/kg), magnesium (2265.7-2538.4 mg/kg), and manganese (130.2-141.8 mg/kg). Significant site-specific variations were observed: seeds from Jameson Park had higher potassium and calcium concentrations, while Kaydale seeds had higher zinc and iron concentrations. Soil analyses revealed no significant differences in phosphorus, nitrogen, zinc, copper, exchange acidity, or total cation concentrations between the sites. However, calcium levels were significantly higher in Jameson Park soils, while Kaydale soils showed higher potassium, magnesium, and manganese concentrations. Soil nutrient concentrations were found to have a significant influence on seed nutrients. These findings emphasise the potential of E. curvula seeds to improve food security and alleviate micronutrient deficiencies, particularly among vulnerable populations such as young children.